1993
DOI: 10.1021/j100140a038
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizer-mediated photoluminescence quenching in quantum-confined cadmium sulfide clusters

Abstract: In this account the influence of charge possessed by the stabilizing medium on the steady-state quenching behavior of quantum confined cadmium sulfide (Q-CdS) semiconductor clusters is reported. Q-cluster stabilizers such as the inverse micelle/hexametaphosphate (HMP) system and thiophenol caps, which afford an anionic solution/stabilizer interface, permit quenching of the integrated trap photoluminescence (PL) intensity (Amx between 550 and 650 nm) up to -45% (HMP) or 54% (thiophenol) by the cation methyl vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…In agreement with the earlier observations, 7c-e the typical absorption and emission spectra of the CdS particles incorporated into DHP vesicles unambiguously indicated the quantum-sized characteristics (Figure ) with an average diameter of about 5 nm. 1a, Although CdS particles were formed on both sides of the DHP vesicles, previous studies pointed out that only those CdS particles were emissive which were located at the interior vesicle surfaces. 7e,8a The emission maximum at 514 nm indicates a predominantly excitonic fluorescence . Similar fluorescence properties were observed with quantum-sized CdS particles prepared in montmorillonite clay and in Langmuir−Blodgett films, probably as a consequence of the tight packing in these systems.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the earlier observations, 7c-e the typical absorption and emission spectra of the CdS particles incorporated into DHP vesicles unambiguously indicated the quantum-sized characteristics (Figure ) with an average diameter of about 5 nm. 1a, Although CdS particles were formed on both sides of the DHP vesicles, previous studies pointed out that only those CdS particles were emissive which were located at the interior vesicle surfaces. 7e,8a The emission maximum at 514 nm indicates a predominantly excitonic fluorescence . Similar fluorescence properties were observed with quantum-sized CdS particles prepared in montmorillonite clay and in Langmuir−Blodgett films, probably as a consequence of the tight packing in these systems.…”
Section: Resultssupporting
confidence: 91%
“…For the preparation and stabilization of quantum-sized CdS particles microheterogeneous systems, such as polyelectrolytes, reverse micelles 1c, or vesicles have in many cases routinely been used. Synthetic bilayer vesicles are attractive models for the study of transmembrane processes including electron-transfer reactions, artificial photosynthesis, and physiological membrane permeability as well.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum confinement effects in semiconductor systems with we reported that cadmium sulfide particulate films composed of highly oriented rod-like CdS nanocrystals can be prepared reduced space dimensions have attracted considerable attention. [1][2][3][4][5][6][7][8][9] In this field, it is very important to assemble semicon-at the monolayer/subphase interface by exposing the stearic acid Langmuir monolayer-coated salt solution to hydrogen ductor nanocrystals in an orderly form and, at the same time, maintain the properties of each individual nanoparticle.9-13 sulfide gas. The generation of CdS was proved by the Auger electron spectrum.…”
mentioning
confidence: 99%
“…The effective mass approximation and, hence, Eqn (11) become inapplicable for small nanoparticles. The observed values of the exciton energies of nanoparticles appear to be lower than those predicted from Eqn (11). A more exact expression for the exciton energy can be found by quantum-chemical methods.…”
Section: E N X Yn Y Ynmentioning
confidence: 66%
“…1,2,110 The first term on the right of the equation is predominant, and its nature was considered above, the second term takes into account the Coulomb interaction between the electron and hole inside the nanoparticle, and the third term is responsible for the spatial correlation. The n values larger than 1 in Eqn (11) correspond to the exciton transitions to higher excited states (see Fig. 8 a).…”
Section: Ntmentioning
confidence: 99%